PENYESUAIAN DIRI PADA SANTRI BARU DI PONDOK PESANTREN - Hasanah, Muhimmatul (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: Students’ lives in pesantren are very different from their lives at home, and they need to adjust to survive until the end of the study period. The strict schedule has a further impact on children’s lives. The many activities are also a problem for some students to adjust to boarding school life. Objective: The purpose of the study is to find out how santri adjust to boarding school activities, as well as the types of behavior shown by new santri in adjusting to their new environment and boarding school activities. Method: This research uses a type of qualitative research with a case study approach. Data analysis techniques use the Miles and Huberman interactive model. Result: The results showed that new santri need motivation from themselves, family, and the environment to be able to adjust more easily. New students find it difficult to adjust only at the beginning of entering the dormitory. Conclusion: New students overcome this problem by building good relationships with the dormitory environment such as making friends with fellow new students, administrators, and the surrounding community.